Gated communities and water: Conflict in San Miguel de Santo Domingo de Heredia (2012-2018) - Montagnini Salazar, Fabricio (2019)
This article is based on collective actions against gated communities in San Miguel, Santo Domingo of Heredia. The main reason for opposition is the impact on aquifers and the use of water by this kind of urbanizations. The purpose of the article is to show how the power relations between economic, political and community actors impact the manner of managing the water. For this reason, different community actors were interviewed, as well as a review of news and institutional documents to narrate and understand the conflict in the area. The information collected shows how gated communities, accompanied by a guarantee from the local government, have allowed public-private alliances for water management, even in a special protection area for this kind of construction. In conclusion, this case is a structural impact of recent changes in land use at provincial level with the passage of coffee plantations to a real estate income, but it found the resistance of community actors who have experienced problems of scarcity and water pollution as well as a tension between market visions in contrast to a use public of water.